(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Paradigm changes in the world of education encourage tertiary institutions to make adjustments, this is no exception for university educational institutions. Especially for private universities, understanding the needs of potential customers is important. This study aims to look for factors that can encourage prospective students to decide on choosing the college they enter. This research was conducted by distributing questionnaires that had been entered at private universities in Malang City. The number of samples in this is 398 respondents. The analytical tool used in this research is exploratory factor analysis. The results of the study show that marketing is a factor that shapes the decision to select a private university in the city of Malang. In this marketing mix there are seven factors consisting of, product, price, promotion, place, physical evidence, process and people. Of the 7P factors, six of them become factors that shape university selection decisions, namely product, price, promotion, place, physical evidence, and people. Meanwhile, in the process factor, the factor analysis cannot be a factor forming a university selection decision, this can be seen from the KMO value which is less than 0.5 Keywords: factor of choosing a private university, marketing mix